Ways to Improve the Mineral Replacement Tax System: Taking the Experience of Commonwealth of Independent States Countries - Ivanova, Yana; Nikeryasova, Veronika; Balikhina, Nella; Savrukov, Aleksey (International Journal of Energy Economics and Policy, 2018)
This article is a critical analysis of mining taxation in Commonwealth of Independent States (CIS). The paper outlines recommendations for improving the tax legislation so that the mineral replacement tax would be calculated in an easy and transparent way for any kind of solid mineral raw material. The first recommendation is to change the tax calculation methodology, tax rates, then –to introduce various benefits (in case of low profitability, in cases depending on the mining conditions, etc.). As a result, this can contribute to the reduction of tax burden, imposed on low-profit mining enterprises, while on the other hand – to increase the tax revenues under favorable market conditions. Keywords: taxation, severance tax, super profit, rental payment, license trade, auction-based system, energy economics. JEL Classifications: H21; N50; P18.